How far is Vienna from Chicago? An essay on the methodology of two schools of dogmatic liberalism - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
From the 194O's until the late 196O's,the unchallenged ruler of the intellectual kingdom of economics was a paradigm which - for lack of a better name - we shall simply call mainstream economics. Broadly speaking, mainstream economics may be described as a well-composed menu of quite distinct analytical tool-boxes which are eclectically used to solve the relevant problems at hand: neoclassical theory in the microeconomic domain, keynesian theory in the macroeconomic domain, and paretian welfare theory in the domain of normative economics.
Keywords: 330